Analysis of Medical Breast Cancer Completeness Under Chemotherapy Resume at Dharmais National Cancer Center - Nursiah Nursiah; Rokiah Kusumapradja; Fresley Hutapea (Journal of Multidisciplinary Academic, 2021)
The background of this study is a return of INACBG's claim rate files inpatient at the National Cancer Centre Dharmais Hospital was still high, where the highest return was due to the confirmation of medical coding and resume. The potential to cause losses for the hospital as a result of delayed claim payments. This study aimed to analyse the completeness of the medical resume which includes the accuracy of the components of the diagnosis, procedure and coding of the INA-CBG's inpatient claim rate at the National Cancer Centre Dharmais Hospital. In this study, we proposed a qualitative approach was used with in-depth interview techniques and a review of the medical resumes of breast cancer patients who received chemotherapy during June-July 2020. From the results, we obtain that the highest incompleteness in filling out medical resumes was related to filling in the indication for admission to care with a percentage of 68, 33%, physical examination 33.33%, and supporting examination 6.67% of the total 60 cases studied. The incompatibility rate of writing a secondary diagnosis was 30% and the procedure/action was 28.33%. Writing the main diagnosis between the medical record and medical resume was known to be in accordance. The main diagnosis coding inaccuracy was still found, with a percentage of 13.33%. The result of the inaccuracy of the main diagnosis coding was a secondary diagnosis mismatch and a procedure / action incompatibility, which resulted in a claim difference of IDR 133,763,800. Therefore, the commitment of the management of the Dharmais Cancer Hospital, namely the team involved in the final coding which was the hospital's internal team should be further strengthened in order to improve the quality of the claim file from the aspects of completeness and accuracy of diagnosis, procedure and coding so that the accurate INA-CBG claim value can be obtained.